Elemental Profiling of Surface Water around Dhaka City by Laser Induced Breakdown Spectroscopy - Ahmed, MF; Abedin, KM; Sadat, ME; Talukder, AI; Wahadoszamen, M; Haider, AFMY (Journal of Bangladesh Academy of Sciences, 2010)
Using the technique of Laser Induced Breakdown Spectroscopy (LIBS), which uses a pulsed laser to create plasma and advanced spectroscopic techniques, we analyzed the contents of surface water (river water) around the city of Dhaka. Several elements such as Li, C, Na, Mg, Al, K, Ca, Ti, Mn, Fe, Sr were identified in the water samples collected in addition to Cr, which was found at two locations at different concentrations. Chromium is a toxic element, and its presence at high concentrations is hazardous for human beings as well as the environment. Its presence in water is suspected due to the effluent discharge from the nearby tanning industries. Semi-quantitative analysis of the chromium present was performed. To our knowledge, this is the first example of the application of the LIBS technique in water analysis in Bangladesh. DOI: 10.3329/jbas.v33i2.4104 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 209-218, 2009